Altered reactivity of resistance vasculature contributes to hypertension in elastin insufficiency - Osei-Owusu, Patrick (American Physiological Society, 2014)
Elastin (Eln) insufficiency in mice and humans is associated with hypertension and altered structure and mechanical properties of large arteries. However, it is not known to what extent functional or structural changes in resistance arteries contribute to the elevated blood pressure that is characteristic of Eln insufficiency. Here, we investigated how Eln insufficiency affects the structure and function of the resistance vasculature. A functional profile of resistance vasculature in Eln(+/−) mice was generated by assessing small mesenteric artery (MA) contractile and vasodilatory responses to vasoactive agents. We found that Eln haploinsufficiency had a modest effect on phenylephrine-induced vasoconstriction, whereas ANG II-evoked vasoconstriction was markedly increased. Blockade of ANG II type 2 receptors with PD-123319 or modulation of Rho kinase activity with the inhibitor Y-27632 attenuated the augmented vasoconstriction, whereas acute Y-27632 administration normalized blood pressure in Eln(+/−) mice. Sodium nitroprusside- and isoproterenol-induced vasodilatation were normal, whereas ACh-induced vasodilatation was severely impaired in Eln(+/−) MAs. Histologically, the number of smooth muscle layers did not change in Eln(+/−) MAs; however, an additional discontinuous layer of Eln appeared between the smooth muscle layers that was absent in wild-type arteries. We conclude that high blood pressure arising from Eln insufficiency is due partly to permanent changes in vascular tone as a result of increased sensitivity of the resistance vasculature to circulating ANG II and to impaired vasodilatory mechanisms arising from endothelial dysfunction characterized by impaired endothelium-dependent vasodilatation. Eln insufficiency causes augmented ANG II-induced vasoconstriction in part through a novel mechanism that facilitates contraction evoked by ANG II type 2 receptors and altered G protein signaling.